The clinical significance of soluble human leukocyte antigen class-I, ICTP, and RANKL molecules in multiple myeloma patients. - Schütt, P; Rebmann, V; Brandhorst, D; Wiefelspütz, J; Ebeling, P; Opalka, B; Seeber, S; Nowrousian, MR; Moritz, T; Grosse-Wilde, H (2008)
Because of the variable clinical course of multiple myeloma, the identification of prognostic parameters is of clinical interest. Therefore, we analyzed the clinical significance of serum levels of soluble human leukocyte antigen class I molecules (sHLA-I), carboxy-terminal telopeptide of type-I collagen (ICTP), and receptor activator of nuclear factor kappa B ligand (RANKL). Compared with controls, sHLA-I were threefold (p < 0.001) elevated in multiple myeloma. Increased levels of ICTP and RANKL were demonstrated in 50 and 43% of patients, respectively. sHLA-I correlated significantly with stage of disease. Serial determination of sHLA-I in 11 patients revealed significantly higher sHLA-I levels (median [range] mug/l) during active disease than during remission (700 [250-2090] versus 380 [130-920]). ICTP demonstrated an association with stages of disease and the presence of osteolytic lesions, whereas there were no differences with respect to active/remittent disease. Importantly, levels of sHLA-I > or = 1000 microg/l and ICTP > or = 5 microg/l were significantly associated with a poor overall survival. For RANKL, no significant associations were observed with disease stages, disease status, osteolytic lesions, and survival. In conclusion, sHLA-I and ICTP serum levels seem to be of prognostic significance in multiple myeloma and might be helpful to identify patients of poor prognosis.